2022
DOI: 10.1109/access.2022.3163273
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Task Scheduling in Cloud Environment Using Decision Tree Algorithm

Abstract: In recent years, Cloud computing has been developed and become the foundation of a wide range of applications. It allows users to access a catalog of standardized services and respond to their business needs flexibly and adaptively, in the event of unforeseen demands, paying solely for the consumption they have made. Task scheduling problem is considered one of the most critical cloud computing challenges. The problem refers to how to reasonably order and allocate the applications tasks provided by the users t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…The transactive operational framework in optimizing IDC operations and energy utilization in geo-distributed markets. [48] Multiobjective task scheduling approach in the cloud environment using the Decision Tree algorithm. It optimizes task allocation.…”
Section: Ref No Methodology Novelty Resultsmentioning
confidence: 99%
“…The transactive operational framework in optimizing IDC operations and energy utilization in geo-distributed markets. [48] Multiobjective task scheduling approach in the cloud environment using the Decision Tree algorithm. It optimizes task allocation.…”
Section: Ref No Methodology Novelty Resultsmentioning
confidence: 99%
“…In [10], a novel Task Scheduling-Decision Tree (TS-DT) algorithm for assigning and implementing application's task was presented. Also an elaborate comparative study was provided and validation results found improvement not only in terms of makespan but also resulted in the improvement of resource utilization.…”
Section: Related Workmentioning
confidence: 99%
“…Before responding to the early warning signal, it is necessary to first transmit the parameters, positions and other data in the detection area to the microcontroller, and then send an alarm by the buzzer after A/D conversion. In practice, the short-time geological radar velocimeter we designed is developed to measure the velocity, thickness and other information of the surrounding environment at different times near some unknown strata [7][8].…”
Section: Demand For Short-time Approaching Forecast and Early Warning...mentioning
confidence: 99%